1985
DOI: 10.1161/01.res.56.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pressure gradients between branches of the left coronary artery on the pressure axis intercept and the shape of steady state circumflex pressure-flow relations in dogs.

Abstract: SUMMARY. When steady state pressure-flow relations are studied in the circumflex coronary artery, pressure gradients develop between it and other branches of the left coronary artery. To assess the effects of these pressure gradients, we compared the pressure axis intercept and shape of steady state circumflex pressure-flow relations in the presence and absence of gradients after autoregulation was abolished, both in the beating heart and during long diastoles in dogs. We used peripheral coronary pressures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 61 publications
4
19
1
Order By: Relevance
“…These mechanical determinants of coronary resistance yield a pressure-flow relation that is straight in the physiological range of arterial pressures, but is curvilinear for pressures below 40 mmHg. This has been clearly demonstrated by observations on pressure-flow relations obtained under experimental conditions where collateral effects were absent because of lack of a pressure gradient between the epicardial arteries (7,13,19). Moreover, the coronary pressure-flow relation is also shifted rightward in ventricles with elevated wall stress, e.g., because of hypertrophy, again without any contribution of collateral flow (12).…”
Section: Discussionmentioning
confidence: 81%
“…These mechanical determinants of coronary resistance yield a pressure-flow relation that is straight in the physiological range of arterial pressures, but is curvilinear for pressures below 40 mmHg. This has been clearly demonstrated by observations on pressure-flow relations obtained under experimental conditions where collateral effects were absent because of lack of a pressure gradient between the epicardial arteries (7,13,19). Moreover, the coronary pressure-flow relation is also shifted rightward in ventricles with elevated wall stress, e.g., because of hypertrophy, again without any contribution of collateral flow (12).…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, we did not measure myocardial tissue blood flow. However, Messina et al (36) reported that collateral blood flow begins to contribute significantly to myocardial tissue blood flow when intercoronary pressure gradients exceed 70 mmHg. In the present study, during exercise mean aortic pressure was in the range of 100-110 mmHg while the pressure at zero flow was in the range of 30-40 mmHg, which would suggest that the collateral driving pressure was probably not sufficient to result in a considerable contribution of collateral blood flow to total myocardial tissue flow.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic autoregulatory mechanisms adjust tone within the microvasculature to maintain distribution of myocardial blood flow over a range of oxygen supply and demand requirements (9). Factors that are involved include intra-and extravascular compressive forces (12,13), left ventricular (LV) preload and afterload (14), LV volume, coronary collateral blood flow (15), neuronal status (16,17), arterial structure (18), and endothelial function (19); these factors can be modulated significantly under physiologic or pathologic conditions. Although it is established that underlying cardiac disease compromises kidney function in humans, it is not clear how impaired renal function affects coronary blood flow regulation, myocardial blood flow distribution, and cardiovascular reserve.…”
mentioning
confidence: 99%